2003
DOI: 10.1016/s1525-0016(03)00103-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activities of an oncolytic adenoviral vector designed to express GM-CSF

Abstract: Oncolytic adenoviruses are being tested as biological cancer therapeutics. Ar6pAE2fF (E2F vector) contains the E2F-1 promoter to regulate the expression of the E1a gene in cells with a disregulated retinoblastoma pathway. Ar6pAE2fmGmF (E2F-GM vector) includes the murine granulocyte-macrophage colony-stimulating factor (GM-CSF) transgene to enhance anti-tumor activity. Both vectors selectively killed human tumor cells in vitro. The E2F-GM vector expressed biologically active murine GM-CSF in vitro and GM-CSF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 19 publications
2
60
0
1
Order By: Relevance
“…Biological activity of GM-CSF was measured in TF-1 cells as described previously. 23 In vivo antitumor efficacy studies Antitumor efficacy studies were performed using tumor xenografts. Xenograft models were established in 6-to 8-week-old female nude mice subcutaneously injecting 2 Â 10 6 of SCC9 or Hep3B cells in Matrigel (injection volume of 0.2 ml).…”
Section: Gm-csf Productionmentioning
confidence: 99%
“…Biological activity of GM-CSF was measured in TF-1 cells as described previously. 23 In vivo antitumor efficacy studies Antitumor efficacy studies were performed using tumor xenografts. Xenograft models were established in 6-to 8-week-old female nude mice subcutaneously injecting 2 Â 10 6 of SCC9 or Hep3B cells in Matrigel (injection volume of 0.2 ml).…”
Section: Gm-csf Productionmentioning
confidence: 99%
“…Bristol et al has used oncolytic adenoviruses to express granulocyte-macrophage colony-stimulating factor (GM-CSF). They found that oncolytic adenovirus with GM-CSF elicited greater efficacy compared to oncolytic adenovirus in an animal model with HCC tumor [35]. Genes coding for inducer of apoptosis such as tumor necrosis factor-related apoptosisinducing ligand (TRAIL), second mitochondria-derived activator of caspases (Smac), and Mda7/IL-24 have been incorporated into oncolytic adenovirus.…”
Section: Oncolytic Viruses For Gene Therapy Of Cancermentioning
confidence: 99%
“…9 Potential anticancer transgenes include tumor suppressor genes, for example, p53; 10 immunomodulatory genes, for example, granulocyte macrophage colony-stimulating factor (GM-CSF) 11,12 and interleukin-24; 13 pro-drug-converting enzymes, for example, thymidine kinase 14 and cytosine deaminase 15 and proapoptotic genes, for example, tumor necrosis factor-a 16 and TRAIL. 17 Several strategies for arming the vectors and for controlling transgene expression have been used, with the most recent attempts utilizing adenoviral promoters and transcriptional control elements to regulate the expression of inserted transgenes.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 This tumor-specific transgene expression improves the safety of the vector. Several insertion sites, such as the E3A region 11,18,22 and E3B region, 15,18 were identified on the basis of detailed knowledge of transcription in adenoviruses. More recently, a novel transposonbased mechanism has been described that identified other potential insertion sites, even though the exact transcriptional regions had not been previously identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation